2007
DOI: 10.1348/147608306x109654
|View full text |Cite
|
Sign up to set email alerts
|

Young people's experiences of individual psychoanalytic psychotherapy

Abstract: Greater emphasis is currently being placed on user involvement in shaping the delivery of mental health services and the need for increasing the evidence base for psychotherapeutic interventions such as individual psychoanalytic psychotherapy (IPP). This qualitative study reports on the range of experiences of six young people aged between 16 and 21 years in undertaking IPP. Interpretative phenomenological analysis was used to develop an in-depth understanding of their experiences. The themes identified the yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 28 publications
6
68
1
2
Order By: Relevance
“…Nonetheless, several studies did not provide sufficient detail on issues such as justification of the research design ( n = 3; Iachini, Hock, Thomas, & Clone, ; Molesworth & Crome, ; Street, ), recruitment strategy ( n = 6; Lee et al, ; LeFrançois, ; Ma & Lai, ; Molesworth & Crome, ; Offord, Turner, & Cooper, ; Street, ), data collection ( n = 3; LeFrançois, ; Molesworth & Crome, ; Street, ), the relationship between researcher and participants ( n = 14; Buckley et al, ; Harper, Dickson, & Bramwell, ; Hart, Saunders, & Thomas, ; Iachini et al, ; Kovshoff et al, ; Lee et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Oruche, Downs, Holloway, Draucker, & Aalsma, ; Pelto‐Piri, Engstrom, K., & Engstrom, ; Street, ; Tam‐Seto & Versnel, ; Wisdom, Clarke, & Green, ), ethical issues ( n = 4; Abrines‐Jaume et al, ; LeFrançois, ; Molesworth & Crome, ; Wisdom et al, ) and rigour of data analysis ( n = 4; Hart et al, ; LeFrançois, ; Molesworth & Crome, ; Street, ). Finally, contribution to research, knowledge or policy was not discussed in two studies (Molesworth & Crome, ; Street, ), new areas of research were not identified in six studies (Buckley et al, ; Hart et al, ; Lee et al, ; Molesworth & Crome, ; Pycroft, Wallis, Bigg, & Webster, ; Street, ) and generalizability of findings was not taken into account in nine studies (Buckley et al, ; Bury, Raval, & Lyon, ; Coyne et al, ; Kovshoff et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Pelto‐Piri et al, ; Street, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, several studies did not provide sufficient detail on issues such as justification of the research design ( n = 3; Iachini, Hock, Thomas, & Clone, ; Molesworth & Crome, ; Street, ), recruitment strategy ( n = 6; Lee et al, ; LeFrançois, ; Ma & Lai, ; Molesworth & Crome, ; Offord, Turner, & Cooper, ; Street, ), data collection ( n = 3; LeFrançois, ; Molesworth & Crome, ; Street, ), the relationship between researcher and participants ( n = 14; Buckley et al, ; Harper, Dickson, & Bramwell, ; Hart, Saunders, & Thomas, ; Iachini et al, ; Kovshoff et al, ; Lee et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Oruche, Downs, Holloway, Draucker, & Aalsma, ; Pelto‐Piri, Engstrom, K., & Engstrom, ; Street, ; Tam‐Seto & Versnel, ; Wisdom, Clarke, & Green, ), ethical issues ( n = 4; Abrines‐Jaume et al, ; LeFrançois, ; Molesworth & Crome, ; Wisdom et al, ) and rigour of data analysis ( n = 4; Hart et al, ; LeFrançois, ; Molesworth & Crome, ; Street, ). Finally, contribution to research, knowledge or policy was not discussed in two studies (Molesworth & Crome, ; Street, ), new areas of research were not identified in six studies (Buckley et al, ; Hart et al, ; Lee et al, ; Molesworth & Crome, ; Pycroft, Wallis, Bigg, & Webster, ; Street, ) and generalizability of findings was not taken into account in nine studies (Buckley et al, ; Bury, Raval, & Lyon, ; Coyne et al, ; Kovshoff et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Pelto‐Piri et al, ; Street, ).…”
Section: Resultsmentioning
confidence: 99%
“…This may lie more with refining multiagency service provision (Joint Commissioning Panel for Mental Health [JCPMH], 2013) rather than direct clinical intervention. Engagement may be facilitated by clinicians discussing cognitive preparedness (Bury et al, 2007), with adolescents at initial attendance. By making sense of help seeking (Reder & Fredman, 1996), and avoiding separating this from engagement, clinicians may develop understanding of client's idiosyncratic engagement facilitators and/or barriers.…”
Section: Discussionmentioning
confidence: 99%
“…In order to engender openness during interviews, the interviewer (IB) was neither a member of the STAR‐Trial research team nor an NHS employee. We acknowledge the dynamic interplay between researcher and participant and how researchers’ beliefs and experiences relating to the topic might be brought to the research process (Bury, Raval, & Lyon, ). SB is a White Australian woman, a clinical academic, and practicing clinical psychologist who has worked with people experiencing psychosis for nearly 15 years.…”
Section: Methodsmentioning
confidence: 99%